INVESTIGATING TEACHER’S HIGHER ORDER THINGKING SKILLS STRATEGIES IN EFL TEACHING READING AT VOCATIONAL SCHOOL CONTEXT - Rachmatul Hikmah; Susilawati Susilawati; Eline Rozaliya Winarto (National Conference on Language, Education, and Technology Proceeding, 2022)
The current study intends to investigate the strategies used by teachers to improve students' higher order thinking skills in teaching reading and to investigate the challenges faced by teachers in improving students' higher order thinking skills in teaching reading of One Vocational School in Cirebon. This research uses descriptive qualitative research. The subject of the research was one English teacher who teaches in two classes in tenth grade students of One Vocational School in Cirebon. Data collection are obtained through observation and interviews. The findings show that the number of strategies used by teacher is five types of teaching strategies, namely informing learning objectives, divergent questions, group discussions, giving feedback, and motivating. The researcher also found four challenges faced by teacher was time, students learning ability, students mastery, and planning domain. This happens because students still do not understand higher order thinking skills. It is suggested that the teacher must encourage active learning and always motivate students.